Organisasi dengan Kepuasan Kerja Hubungan Iklim Organisasi dengan Kepuasan Kerja Perawat di Rumah Sakit Pertamina Jaya Jakarta - Lenny Rosbi Rimbun (STIKes Persada Husada Indonesia, 2016)
Conducive organizational climate associated with conformity, responsibility, standards, rewards, organizational clarity, warmth, support, and leadership will make satisfaction in work, it is not perceived by nurses at Pertamina Jaya Hospital in Jakarta illustrated turnover rate tends to increase, not there is no certainty to be appointed as a permanent employee, you want to get the award. The purpose of this study was to determine the relationship with job satisfaction organizational climate nurse. This research uses descriptive correlation study with a sample of 129 nurses. Data were collected by questionnaires and analyzed using Chi Square test and multiple logistic regressions. Results obtained the significant relationship between organizational climate (conformity, organizational clarity, warmth and support leadership) with nurse job satisfaction on p = 0000-0019; α = 0.05, and the most dominant variable was the variable of leadership. Good leadership has the opportunity to work feeling satisfied, where nurses receive further guidance or input nurses feel supported , valued and get a solution if they find problems in the execution of their duties.